(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
This paper aims to contribute to the exploration o f the productive relationships between philosophy, law and literature, in the spirit o f the contemporary “Law and Literature " movement. More specifically, it analyses the key leitmotifs o f the famous mystery novel “And Then There Were None" by Agatha Christie, revealing their potential to illustrate the complexity and the deep existential relevance of some o f the most important questions tackled by the philosophy o f law as a discipline. The specific interconnectedness o f the ideas o f justice, guilt, crime, revenge and punishment, reflected by the complicated structure o f the plot o f Christie’s novel, is viewed as an opportunity’ to test and further refine our fundamental intuitions about the principles o f justice and their practical application.